A case-control study on oral health knowledge and dental behavior among individuals with developmental delays in Jordan: caregiver perspective - Alshatrat, Sabha Mahmoud; Al-Omari, Wael Mousa; Tabnjh, Abedelmalek Kalefh; Al-Bakri, Isra Abdulkarim; Selvaraj, Siddharthan (Frontiers in Dental Medicine, 2024)
Aim: the aim of this study is to assess oral health knowledge and dental behavior among individuals with developmental delays intellectual and developmental disabilities (IDD) in comparison with individuals without (IDD) in Jordan. Methods: A case–control study was conducted among 317 caregivers of individuals with IDD (n=168) and control (n=149) groups, which involved the completion of the questionnaire. A closed-ended, validated self-designed questionnaire was distributed. The questionnaire included questions addressing participants’ oral health knowledge and behavior. Convenience sampling was used to select the caregivers from centers associated with IDD by collecting data from nearby locations. Using SPSS® software Version 22 with a 0.05 level of significance data were analyzed. A Chi-square test and contingency-table analysis were performed on the data. Results: Caregivers for individuals with IDD in Jordan were less knowledgeable about different oral health aspects than control group (p value < 0.05). Fewer individuals in the IDD caregiver group brushed their teeth once or twice daily (83.2%), compared to the control group (93.3%). Only 22.6% of the IDD participants could brush their teeth without assistance. On the other hand, the IDD group consumed significantly less sugary foods and soda than the control group (P value < 0.05). Conclusion: The lack of knowledge among IDD caregivers in Jordan is critical which can result in poor oral health outcomes for this vulnerable population. Increasing the knowledge level for the IDD caregivers on the specific needs for IDD individuals is highly important to enhance their understanding of oral health and improve their quality of life. Caregivers with IDD should receive training programs given by oral health professionals about the need for regular dental check-up and effective oral hygiene care reduce the risk of having dental problems and oral disease.